Self-Report Hearing and Injury or Falls in Older Adults from the National Health and Information Survey - Powell, Danielle S.; Morales, Emmanuel E. Garcia; Pletnikova, Sasha; Deal, Jennifer A.; Reed, Nicholas S. (Seminars in Hearing, 2021)
This article aims to investigate the association between hearing and nonfatal injury or falls in a nationally representative sample of adults from the National Health Interview Survey (NHIS) utilizing over 20 years of participant surveys. We conducted a pooled cross-sectional analysis of participant surveys (aged 50 years and older) from 1997 to 2017. Self-report hearing difficulty, history of injury over the last 3 months, reported injury from fall over the last 3 months, and reported reason for fall (including due to balance/dizziness) were collected. Using logistic regression, we investigated the odds of injury, injury from fall, and fall due to balance/dizziness by self-report hearing status. In secondary analysis, we investigated the odds of each outcome by reported hearing aid use. Models were adjusted for demographics, year of study, vision difficulty, diabetes, employment, and cardiovascular disease. Reported moderate or greater difficulty hearing demonstrated a significantly greater odds of injury (odds ratio [OR]: 1.29; 95% confidence interval [CI]: 1.18, 1.42) or fall due to balance/dizziness (OR: 1.26; 95% CI: 1.00, 1.60) compared with reported excellent/good hearing. A dose–response association was seen across levels of reported difficulty hearing for all outcomes. In this nationally representative study of adults aged 50 years and older, greater reported difficulty hearing was significantly associated with increased odds of injury and suggests greater odds of falls or fall due to balance/dizziness compared with reported good hearing. Results suggest hearing loss should be considered as a possible risk factor for both injury and fall prevention studies and programming in older adults.
Keywords: hearing; hearing difficulty; injury; falls